Komunikasi Layanan Berbasis Kognitif-Behavior dalam Penanganan Keluhan Pasien di Rumah Sakit Muhammadiyah Palembang - Efrizal Ariansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze cognitive-behavior-based service communication in handling patient complaints at Muhammadiyah Hospital Palembang. Service communication in a hospital context does not only function as a process of delivering information but also as a strategy to help patients understand service situations, manage perceptions, reduce emotional tension, and shape more cooperative communication behavior. The cognitive-behavior approach is used to examine the relationship between patients’ understanding of service information, emotional responses when facing service problems, and patient behavior in expressing complaints. This study employs a descriptive qualitative method, with data collected through interviews, observation, and documentation. The informants consist of information service officers, administrative staff, and patients or patients’ families who have submitted complaints. The findings indicate that clear, empathetic, responsive, and easily understood service communication can help patients interpret complaints more rationally, reduce anxiety, and encourage more open and cooperative communication behavior. Conversely, incomplete information, slow responses, and less communicative service language may generate negative perceptions, dissatisfaction, and more emotional complaint behavior. This study emphasizes that handling patient complaints requires attention to patients’ cognitive, affective, and behavioral aspects. Therefore, cognitive-behavior-based service communication can serve as a strategic approach to improving service quality, patient trust, and hospital image.